1999
DOI: 10.1017/s0022112098003061
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic convection in molten gallium

Abstract: We present the results of an experimental and numerical study of the effects of a steady magnetic field on sidewall convection in molten gallium. The magnetic field is applied in a direction which is orthogonal to the main flow which reduces the convection and good agreement is found for the scaling of this effect with the relevant parameters. Moreover, qualitatively similar changes in the structure of the bulk of the flow are observed in the experiment and the numerical simulations. In particular, the flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…BenHadid & Henry 1997) are symmetric to rotations of π about the y-axis (rotationsymmetry) and to reflections with respect to the L v plane (left-right symmetry). However, in the experimental flows of Hurle, Jakeman & Johnson (1974), Braunsfurth et al (1997) and Juel et al (1999) this rotation-symmetry is not usually observed. As in any physical system, imperfections tend to break the perfect symmetries assumed in models.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…BenHadid & Henry 1997) are symmetric to rotations of π about the y-axis (rotationsymmetry) and to reflections with respect to the L v plane (left-right symmetry). However, in the experimental flows of Hurle, Jakeman & Johnson (1974), Braunsfurth et al (1997) and Juel et al (1999) this rotation-symmetry is not usually observed. As in any physical system, imperfections tend to break the perfect symmetries assumed in models.…”
Section: Resultsmentioning
confidence: 95%
“…In a combined numerical and experimental study, Juel et al (1999) measure the vertical temperature difference at a given Grashof number for varying Hartmann numbers in a transverse applied field. Experimental and numerical results show excellent agreement and, in particular, flows observed in the calculations become increasingly two-dimensional with increasing Hartmann number.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the average Nusselt number increases with Marangoni number, but decreases with Hartmann number. Some notable studies on the numerical simulation of combined buoyancy and/or thermocapillary convection in a differentially heated rectangular enclosures are due to Strani et al (1983), Srinivasan and Basu (1986), Bergman and Ramadhyani (1986), Bergman and Keller (1988), Juel et al (1999), Moessner and Mueller (1999) and Gelfgat and Bar-Yoseph (2001). The effect of magnetic field on the combined buoyancy and thermocapillary driven convection in a rectangular enclosure containing a heat generating substance has been numerically investigated by Hossain et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In this paper, we provide insight into the damping mechanisms at play through the direct computation of Hopf bifurcation points and the analysis of the associated three-dimensional flow solutions. Similar continuation calculations have been performed in the absence of a magnetic field in a rectangular parallepiped enclosure, revealing multiple flow structures depending on the values of the aspect ratios and Prandtl number.…”
Section: Introductionmentioning
confidence: 99%